End to end GUI development with Qt5 : develop cross-platform applications with modern UIs using the powerful Qt framework /: develop cross-platform applications with modern UIs using the powerful Qt framework. (2018) - Sherriff, Nicholas; Lazar, Guillaume; Penea, Robin; Piccolino, Marco
No abstract available